Integration of Cultural Literacy in Listening Skills Based on Local Wisdom - Agita Misriani; Farida Isroani; Shesilia Cintari (Jurnal Pendidikan Edutama, 2024)
This research aims to find out Cultural Literacy in Learning Listening Skills containing Wisdom and find out how to integrate Cultural Literacy in Learning Listening Skills containing Local Wisdom. National literacy can be tried with educational sessions that can be developed into a cultural literacy. Cultural literacy is tried by increasing literacy activities that use topics about culture and text sources on cultural topics. Cultural competency can be included in all existing scientific disciplines. Local wisdom is a form of activity that is preserved and passed down from generation to generation within a community group. The method used in this research is qualitative descriptive with the research subjects used in this research being people or objects that can provide information in the form of data that is needed. The subjects in this research are the local wisdom of Rejang Lebong and kepahiang. The result of this research is to produce cultural values and goals in the form of listening videos based on local wisdom which have implications for the learning process that supports increasing accreditation scores.